Comparison of the Demographics, Semen Parameters and Hormone Profiles in Men with Primary and Secondary Infertility - Gowri, Vaidyanathan (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2010)
OBJECTIVES: The objectives of this study were to compare the demographics, semen parameters and hormone profiles in men with primary and secondary infertility. METHODS: The study was designed as a retrospective analysis of data collected from men attending a combined infertility clinic (seen together by urologist and gynaecologist) from January 2005 to December 2008 at Sultan Qaboos University Hospital, a tertiary care hospital in Oman. Ninety-eight consecutive male patients with one or more abnormalities in semen analysis were referred to the combined infertility clinic. A complete physical examination was carried out by a urologist followed by hormone evaluation of follicle stimulating hormone (FSH), luteinizing hormone (LH), testosterone (T) and prolactin (PRL). RESULTS: The semen parameters and the sex hormone evaluation were not significantly different between the men with primary and secondary infertility. The men with primary infertility were younger than the men with secondary infertility. A total of 24% of the men in the primary group and 16% in the secondary group were azoospermic with normal gonadotropin values in 9 men and 1 man in the primary and secondary group respectively. CONCLUSION: Azoospermia was more common in the primary infertile group and, based on gonadotropin levels, obstructive causes seemed more prevalent in the primary group compared to secondary group.